The Questionnaire about Interpersonal Difficulties for Adolescents: Reliability and validity evidence in Colombian adolescents (2013)
The aim of this study was to analyze reliability and validity evidence of scores on the Colombian version of the Questionnaire about Interpersonal Difficulties for Adolescents (QIDA) in a sample of 1,628 adolescents (65.7% boys), ranging in age from 12 to 18 years. Confirmatory factor analyses replicated the correlated five-factor structure of the QIDA: Assertiveness, Heterosexual Relationships, Public Speaking, Family Relationships, and Close Friendships. Internal consistency for the QIDA and subscales scores was excellent. Girls reported higher level of perceived anxiety in heterosexual relationships, whereas boys showed more anxiety in close friendships and decreased interpersonal anxiety during adolescence. Results support the reliability and validity of the scores on the Colombian version of the QIDA.